Factors associated with suicidal ideation among schoolchildren in a municipality in the Brazilian Amazon region (Research, Society and Development, 2020)
Objective: this article aimed to identify the presence of suicidal ideation among schoolchildren in a municipality in the Lower Amazon, as well as the factors associated with this outcome. Methodology: this is a cross-sectional analytical study carried out with 363 students from October 2018 to February 2019. The data collected were worked on descriptive statistics, percentage distribution and the Chi-square and Fischer Exact tests. Results: the following variables showed statistical significance: female gender; age between 11 and 14 years; elementary school students; indigenous schoolchildren; they face their problems reasonably / poorly; have a bad relationship with the family; shows little / no interest in the school. Conclusion: this study showed a higher prevalence of suicidal ideation than the statistics found for this age group in other published studies, however, the variables that showed a statistical association with the presence of suicidal ideation mostly coincide with the variables found in other published studies.